Entrepreneur digital business strategy and efficiency: Intervening role of firm' s IT capabilities - Eniola, A. A.; Kenzhin, Zh.; Kairliyeva, G. (Journal of Scientific and Industrial Research. - 2022, 2022)
Organizations change their business strategies by incorporating digital technology where their skills make an important contribution to the contemporary and continually changing world. This analysis is intended to examine the relationship between Digital Business Strategy (DBS) and the efficiency of the Small and Medium Enterprises (SMEs) in Nigeria through the intervening role of Information Technology (IT) capability. The survey is therefore quantitative, and the findings show that DBS has a significant positive effect on the business spanning (p = 0.001), and the coefficient is positive as well. The direct effect of the IT proactive stance is also calculated as a significant positive impact on the efficiency of SMEs (p 0.055). However, all other direct effects are not statistically significant. A complete intervention of IT capability is assessed favourably by business spanning, IT infrastructure and proactive posture. The intervention effect was evaluated using the Structural Equation Modelling (SEM) method. The research has a variety of management inferences, notably for the proactive posture in which managers will facilitate the transition to improve performance.Организации меняют свои бизнес-стратегии, внедряя цифровые технологии, где их навыки вносят важный вклад в современный и постоянно меняющийся мир. Этот анализ предназначен для изучения взаимосвязи между цифровой бизнес-стратегией (DBS) и эффективностью малых и средних предприятий (МСП) в Нигерии с помощью промежуточной роли информационных технологий (ИТ). Таким образом, опрос является количественным, и результаты показывают, что DBS оказывает значительное положительное влияние на охват бизнеса (p
Keywords: импакт-фактор 2022; научный журнал; периодическое издание; зарубежное издание; дальнее зарубежье; скопус; цифровые технологии; бизнес стратегии; зарубежные авторы